2003
DOI: 10.1021/ja0288237
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Crystal Structure of a Water-Soluble Iridium Hydride:  A Robust and Highly Active Catalyst for Acid-Catalyzed Transfer Hydrogenations of Carbonyl Compounds in Acidic Media

Abstract: This paper reports the isolation and structural determination of a water-soluble hydride complex [Cp*Ir(III)(bpy)H](+) (1, Cp* = eta(5)-C(5)Me(5), bpy = 2,2'-bipyridine) that serves as a robust and highly active catalyst for acid-catalyzed transfer hydrogenations of carbonyl compounds at pH 2.0-3.0 at 70 degrees C. The catalyst 1 was synthesized from the reaction of a precatalyst [Cp*Ir(III)(bpy)(OH(2))](2+) (2) with hydrogen donors HCOOX (X = H or Na) in H(2)O under controlled conditions (2.0 < pH < 6.0, 25 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
134
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(143 citation statements)
references
References 19 publications
(11 reference statements)
7
134
0
2
Order By: Relevance
“…[1] The transition-metal-based enantioselective hydrogenation or transfer hydrogenation of ketones in organic solvents [2][3][4][5][6][7][8][9][10] as well as in aqueous solutions [11][12][13][14][15][16][17][18][19][20][21] is one of the most commonly used synthetic approaches. Biotransformations of organic substrates by various enzymes have also found widespread applications, particularly because of their capability to efficiently perform enantioselective transformations.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The transition-metal-based enantioselective hydrogenation or transfer hydrogenation of ketones in organic solvents [2][3][4][5][6][7][8][9][10] as well as in aqueous solutions [11][12][13][14][15][16][17][18][19][20][21] is one of the most commonly used synthetic approaches. Biotransformations of organic substrates by various enzymes have also found widespread applications, particularly because of their capability to efficiently perform enantioselective transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Similar acid-promoted pathways have been invoked for ketone reduction catalyzed by 1. [10] The improved selectivity would also be consistent with the diminished water content in concentrated HCO 2 H solutions, as a higher ratio of HC(OH) 2 + to H 3 O + would disfavor reaction (1). Scheme 1 lays out a plausible pathway for methanol formation supported by the available data.…”
Section: Angewandte Zuschriftenmentioning
confidence: 71%
“…1 H NMR spectroscopic studies revealed that dissolving precatalyst 1 in 3 m HCO 2 H/ D 2 O causes rapid conversion at ambient temperature to a mixture of deuteride [Cp*Ir(bpy)D]OTf (2) [10] and another species in an approximately 9:1 ratio. Electrospray ionization mass spectrometry under the same conditions featured ion peaks for deuteride 2 (m/z 486.2, Figure S22 in the Supporting Information) and identified the minor species as the formate complex [Cp*Ir(bpy)(O 2 CH)]OTf (3, m/z 529.1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both aldehydes and ketones were successfully hydrogenated by H-transfer from aqueous formate using Ru(II)-complexes as catalysts [42][43][44][45][46][47]. Rh(I)-and Ir(I)-complexes are also known to act as catalysts in such reactions [48,49], in fact, Ir(I)-complexes with monotosylated ethylenediamine ligands [9,10] showed outstanding catalytic activities up to turnover frequencies, TOF = 3.0 × 10 5 h −1 (TOF = mol reacted aldehyde × (mol catalyst) −1 × h −1 ) [10].…”
Section: Introductionmentioning
confidence: 99%